The Role of Counsellors in the Education of Youths for National Stability and Integration in Jos North Local Government Area - Namo, Ibuebue S.; Momoh, Grace Ohunene (NIU Journal of Humanities; Vol 4 No 3 (2019): KIU Journal of Humanities, Vol. 4 No. 3, September 2019, 2019)
This paper was meant to ascertain the role of counsellors in the education of youth for national are integration in Jos North Local Government Area, descriptive survey research was used to collect information from preventative sample and draw conclusions concerning targeted population. The population was all youth in Jos North Local Government Area, four ward were randomly selected at twenty youths per ward, eighty youths were used for the sample. The instrument used were labeled Questionnaire for the role of Counsellors in the Education of Youth for National Stability and Integration (QRCEYSI). It was meant to measure causes of division, place of youth in national integration and the role of counsellors in educating youth from national integration and stability in Jos North Local Government Area. Finding revealed that there is a serious division amongst the youth, youth play a great role in integration. There is a yearning for counsellors in the informal and non formal setting for education of different youth for national integration. The following were recommended: Youth from different tribe, religion, political affiliation and social economic statue should work for integration, counsellors should work in creating awareness that can help them to better cooperate and enhance integration and stability, government should involve counsellors in issues of national importance especially in area of peace and reconciliation integration and stability, local government and wards should have counselling unite, youth should be brought together for different social event like football match to foster integration. Keywords: Education of Youths, Integration,  National stability and role of Counsellors